D6.9 Report on visiting experts Seminars and trainings - Antoniou, Theofilos; Pittaki, Zampella; Theocharidis, Christos; Fotiou, Kyriaki; Hadjimitsis, Diofantos G.; Schreier, Gunter (My University, 2023)
Deliverable “D6.9 Report on visiting experts Seminars and trainings” focuses on the implementation of accredited technical short courses to keep ECoE researchers up-to-date with state-of-the-art equipment, new software, models, EO data assimilation techniques, new algorithms, machine learning theory and practice, etc., in a hands-on approach to stimulate innovate research. Several talks have been designed and delivered by invited experts. Finally, an initial training scheme plan that took place during RP3 (M31 – M48) is provided as well as the scheme plan for the upcoming training activities for the period RP4 (M49 – M66).
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; capacity building